Population and development in Uttar Pradesh: a district level analysis using census data - Tiwari, A. K. (International Journal of Health, 2015)
Population and Development is a complex area for research and it includes issues related to many variables, such as demography, economics, urbanization, gender, religion, politics, food and nutrition, health, human rights etc. The Indian census is used to collect extensive data at household level. Wide Information about source of income, information on demographic variables, household belonging, possession of various durable household goods etc. are collected in Census 2011. The present study is an attempt to analyze the population and development in Uttar Pradesh (UP), highly populated state in India. This paper will provide position of all districts of UP in respect of few selected socio- demographic variables. This study concludes that some districts of UP are performing better than many states in the country but some districts are much behind when compared with some develop states and India.